Victor Hugo no Porto finissecular : marcas de um percurso - Carneiro, Maria do Nascimento Oliveira (1997)
The article intends to analyse the projection of Victor Hugo in Oporto at the end of the 19th century, both on the literary-aesthetic level as well as a guide to the gene¬ration which looked forward to the advent of the Republic in Portugal.